Constructing STEM 3R Activity through Service-Learning Program during Movement Restriction - Misiran, Masnita; Ahmad, Nazihah; Md Yusof, Zahayu; Misiran, Maslina (Universiti Pendidikan Sultan Idris, 2022)
Service-learning is an experiential learning activity that enables mobility from classes in higher learning institutions to be transferred into the community. In this article, we construct a STEM 3R activity that is aligned with school children's curricula to be delivered in an engaging, active, and personalized way. The activity is constructed by using the ExDiDD (Explore, Discover, Develop, Deliver) framework, and is being assessed through dedicated rubrics. Findings suggest improved excitement and interest in STEM education, as well as increase understanding of the environmental issues throughout the activity